FAKTOR YANG MEMPENGARUHI PRODUKSI USAHA MIKRO KECIL DAN MENENGAH (UMKM) PRODUK KERIPIK DI KOTA TARAKAN - Ali Lutfi Munirudin; Elly Jumiaty; Nurlela Machmudin (FAKULTAS PERTANIAN UNIVERSITAS BORNEO TARAKAN, 2019)
ABSTRACT Micro Small and Medium Enterprises (SMEs) in Tarakan City is potencially to be developed. One of SMEs many developed is the chips business. According to the data from the Department of Animal Husbandry and Food Crop of Tarakan City in 2016, there were 15 types of SMEs product of chips are scattered throughout the Tarakan city. To develop of SMEs, increasing the production of chips was needed. To reach the maximum level of chips production, the businessmen had to have a complete knowledge about chips production factors which are used. How far was the influence of the chips production inputs to the output. The appropriate production factors use with reaching the level production. This research aimed to (1) Know what factors influence the production of Micro, Small and Medium Enterprises (SMEs) Product of Chips in Tarakan, (2) determine the factors that most affect the production of Micro, Small and Medium Enterprises (SMEs) Product of Chips in Tarakan City. This research was conducted in Tarakan City. The samples which in the study is 15 units Micro, Small and Medium Enterprises (SMEs) which chips produce and the method of data analysis used is path analysis. Intend path analysis to determine the pattern of relationship independent variable (X) which influencing dependent variable (Y), to know the value of relationships and influence done several is Kolmogorov-smirnov test, correlation coefficient test, F test and t test. According to the results of research which was analyzed by using path analysis, we obtained that (R2) was 97,8 persen, means the ability of independent variable inside variance explained from dependent variable. Influencing factors in production were raw materials (X1), equipment (X2), Labor (X3). The influence of raw materials (X1) to production (Y) was 38,7 persen. The influence of equipment (X2) to production (Y) was 3,7 persen. The influence of labor (X3) to production (Y) was 55,3 persen. We could see that the most influential factor to the production of these chips business was the raw labor (X3) with the total effect was 55,3 persen. Keywords: path analysis, product, SMEs ABSTRAK Usaha Mikro, Kecil dan Menengah (UMKM) di Kota Tarakan sangat berpotensi dikembangkan, salah satu diantaranya adalah usaha keripik. Berdasarkan data Dinas Peternakan dan Tanaman Pangan Kota Tarakan 2016, terdapat 15 jenis UMKM produk keripik yang tersebar di seluruh wilayah Kota Tarakan. Untuk pengembangan UMKM ini perlu adanya peningkatan produksi keripik. Untuk mencapai tingkat produksi keripik yang maksimum, pelaku usah harus memiliki pengetahuan yang lengkap atas faktor-faktor produksi keripik yang digunakannya. Sejauh mana pengaruh input produksi keripik terhadap output yang dihasilkan, Tujuan penelitian ini adalah menfaktor apa saja yang mempengaruhi produksi UMKM pada usaha keripik di Kota Tarakan, dan mengetahui faktor yang paling berpengaruh terhadap produksi Usaha Mikro Kecil dan Menengah (UMKM) produk keripik di Kota Tarakan. Sampel yang digunakan dalam penelitian ini adalah 15 unit UMKM yang memproduksi keripik dan metode analisis data yang digunakan adalah analisis jalur. Analisis jalur bertujuan untuk mengetahui pola hubungan variable bebas (X) yang mempengaruhi variable terikat (Y), untuk mengetahui besarnya nilai hubungan dan pengaruhnya dilakukan dengan beberapa cara yaitu uji normalitas, uji koefisien korelasi, uji F dan uji t. Berdasarkan hasil penelitian yang di analisis menggunakan analisis jalur, diperoleh (R2) sebesar 97,8 persen artinya kemampuan variabel bebas dalam menjelaskan varian dari variabel terikat adalah sebesar 97,8 persen. Faktor yang berpengaruh dalam produksi keripik adalah bahan baku (X1) sebesar 38.7 persen, peralatan (X2) 3.7 persen dan tenaga kerja (X3) sebesar 55.3 persen. Dapat kita lihat bahwa faktor yang paling berpengaruh dalam produksi keripik ini adalah tenaga kerja (X3) dengan total pengaruh sebesar 55.3 persen. Kata kunci: analisis jalur, produk, UMKM.